Examining the Impact of Classroom Management, Resource Utilization, and Teaching Strategies on Academic Success in History Education: The Role of Self-Efficacy as a Moderator - Bety D.S. Hetharion (STAI Hubbulwathan Duri, 2025)
Academic self-efficacy plays a critical role in students’ learning outcomes, yet its interaction with instructional variables in history education remains underexplored. This study investigates the influence of classroom management, instructional methods, and learning resource management on students' academic self-efficacy in Indonesian senior high school (SMA) history classes. Using a descriptive quantitative approach, data were collected from 100 randomly selected students representing diverse academic and socioeconomic backgrounds. A structured survey was used to gather data, which were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that classroom management significantly impacts both academic self-efficacy and student performance in history. While academic self-efficacy positively influences students’ engagement and persistence, its moderating effect on the relationship between other variables was found to be statistically non-significant in some cases. Resource availability and instructional quality were also identified as key contributors to improved academic outcomes. The results underscore the importance of a well-managed and resource-rich classroom in fostering student motivation and achievement. Students with higher self-efficacy are more likely to enjoy learning, persevere in academic tasks, and participate actively in class. The study recommends that history educators adopt student-centered approaches—such as project-based learning, digital tools, and collaborative discussions—to enhance learners’ agency and interest. This research contributes to the literature by integrating four theoretical frameworks—Constructivist, Social Cognitive, Learning Resource, and Self-Determination Motivation theories—and highlights the relatively overlooked moderating role of academic self-efficacy in history education.